Discovery of potential attention deficit and hyperactivity disorder (ADHD) drug molecules from natural compounds: In silico studies with Tanimoto similarity - Ertik, Onur (Elsevier Science Inc, 2026)
Attention deficit and hyperactivity disorder (ADHD) is a neurological disorder that prevents individuals from developing their potential and causes an inability to focus, especially in children, and the prevalence of ADHD in adults has been increasing. There is a very limited group of drugs for treatment of ADHD, the most important of which is methylphenidate. Therefore, the discovery of new drug molecules becomes very important because of limited drugs. In this study, methylphenidate molecule was compared with 790096 molecules by utilizing Tanimoto similarity of natural compounds and molecules were identified by second filtering according to blood-brain barrier penetration. Then, molecules were docked with dopamine transporter (DAT) and compounds with better binding scores than methylphenidate were identified and molecular dynamics simulation studies were done for the best pose and validated conformation. In addition, molecular docking and dynamic simulations were performed for monoamine oxidase A and B (MAO-A and MAO-B) in order to control the state of depression frequently encountered in ADHD individuals. The results suggest the compound 3706153 ((octahydro-1H-qui-nolizin-1-yl)methyl 2-(naphthalen-1-yl)acetate) has potentially inhibitory molecule for DAT, MAO-A and MAO-B and have a potential of the main structure in the development of alternative drug molecule for ADHD from the natural compounds.
Keywords: Drug discovery; Dopamine transporter; Monoamine oxidase A and B; ADHD; In silico